Characteristics and associated factors of violence in male patients with schizophrenia in China - Guo, Weilong; Gu, Yu; Zhou, Jiansong; Wang, Xiaoping; Sun, Qiaoling (Frontiers in Psychiatry, 2023)
Objective: To investigate the characteristics and associated factors of violence in male patients with schizophrenia in China. Methods: A total of 507 male patients with schizophrenia were recruited, including 386 non-violent and 121 violent patients. The socio-demographic information and medical history of the patients were collected. Psychopathological characteristics, personality traits psychopathology, and factors related to risk management were assessed using the Brief Psychiatric Rating Scale (BPRS), the History of Violence, Clinical, Risk Assessment Scale (HCR-20), and the Psychopathy Checklist-Revised (PCL-R), as appropriate. Differences in these factors were compared between the violent and non-violent patients, and logistic regression analysis was performed to explore the risk factors for violence in male patients with schizophrenia. Results: The results showed that the violent group had a lower level of education, longer duration of illness, as well as a higher rate of hospitalization, history of suicidal attempts, and history of alcohol compared with the non-violent group. The violent group scored higher in items of symptoms in BPRS, personality traits and psychopathy in PCL-R, and risk management in HCR-20. The regression analysis showed that previous suicidal behavior (OR = 2.07,95% CI [1.06-4.05], P = 0.033), antisocial tendency in PCL-R (OR = 1.21, 95% CI [1.01-1.45], P = 0.038), H2: young age at violent incident (OR = 6.39, 95% CI [4.16-9.84], P <0.001),C4: impulsivity (OR = 1.76, 95% CI [1.20-2.59], P = 0.004), and H3: relationship instability (OR = 1.60, 95% CI [1.08-2.37], P = 0.019) in HCR-20 were risk factors of violence among male patients with schizophrenia. Conclusions: The present study found significant differences in socio-demographic information, history of treatment, and psychopathy characteristics between male patients with schizophrenia who had engaged in violent behaviors and their non-violent counterparts in China. Our findings suggested the necessity of individualized treatment for male patients with schizophrenia who had engaged in violent behaviors as well as the use of both HCR-20 and PCL-R for their assessment.